The Helmholtzian Operator and Maxwell-Cassano Equations of an Electromagnetic-nuclear Field - Cassano, Claude Michael (Edelweiss Applied Science and Technology, 2019)
This article demonstrates that when acting on a four-vector doublet, the Helmholtzian may be factored into two 4×4/8×8 differential matrices, resulting in a four-vector doublet Klein-Gordon equation with source. This factorization enables yielding of a mass-generalized set of Maxwells equations.